2014
DOI: 10.1021/nn501284q
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur-Infiltrated Graphene-Based Layered Porous Carbon Cathodes for High-Performance Lithium–Sulfur Batteries

Abstract: Because of advantages such as excellent electronic conductivity, high theoretical specific surface area, and good mechanical flexibility, graphene is receiving increasing attention as an additive to improve the conductivity of sulfur cathodes in lithium-sulfur (Li-S) batteries. However, graphene is not an effective substrate material to confine the polysulfides in cathodes and stable the cycling. Here, we designed and synthesized a graphene-based layered porous carbon material for the impregnation of sulfur as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
225
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 375 publications
(234 citation statements)
references
References 46 publications
8
225
0
1
Order By: Relevance
“…All the capacity retention and capacity degradation are calculated from the third cycle after achieving stabilized capacity. The achieved cycling ability in Figure 5c,d is much better than that of most previous reports 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 48. Only very recently, Cui and co‐workers51 successfully demonstrated that the TiO 2 /S yolk–shell composites can be cycled over 1000 times with a capacity decay of 0.033% per cycle.…”
Section: Resultsmentioning
confidence: 51%
See 4 more Smart Citations
“…All the capacity retention and capacity degradation are calculated from the third cycle after achieving stabilized capacity. The achieved cycling ability in Figure 5c,d is much better than that of most previous reports 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 48. Only very recently, Cui and co‐workers51 successfully demonstrated that the TiO 2 /S yolk–shell composites can be cycled over 1000 times with a capacity decay of 0.033% per cycle.…”
Section: Resultsmentioning
confidence: 51%
“…Even after cycling for 600 cycles, the battery still gives a specific areal capacity of 1.6 mAh cm −2 . However, the specific areal capacity in most previous reports13, 16, 20, 21, 23, 26, 28, 30, 39, 40, 43, 45, 51 is lower than 2 mAh g −1 due to the low sulfur loading in the electrodes (see Table S1 in the Supporting Information and corresponding discussion). Moreover, some previous superior cycling performances over 500 cycles20, 43, 45, 51 are achieved by low sulfur loading, which is usually lower than 1 mg cm −2 (Table S1, Supporting Information), while in our present work, the electrode with 2.7 mg cm −2 sulfur loading can still run over 600 cycles.…”
Section: Resultsmentioning
confidence: 88%
See 3 more Smart Citations